Analisis Strategi Pengembangan Usaha Bunga Krisan Potong di CV Imunk Flower Kecamatan Bandungan Kabupaten Semarang - Ningsih, Tika Lestari; Handayani, Migie; Herista, Mutia Intan Savitri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
CV. Imunk Flower is a chrysanthemum cultivation company in Bandungan District, established in 2012 and officially registered as a limited partnership (CV) in 2022. The large number of chrysanthemum farmers in the area causes peak harvest periods and price fluctuations, creating marketing challenges. Limited promotion and a shortage of administrative staff also hinder sales performance. This study aims to identify internal and external factors influencing business development, analyze strategies for developing cut-chrysanthemum agribusiness, and determine priority alternative strategies for CV. Imunk Flower. The research was conducted from May to June 2025 using a case study approach. Primary data were obtained through interviews with structured questionnaires and direct observation, while secondary data were collected from literature and company documents. Purposive sampling was used to select informants, consisting of the owner, 7 workers, saprotan suppliers, and 10 consumers. Data were analyzed using descriptive quantitative methods with the IFAS, EFAS, and SWOT matrices, as well as the Analytical Hierarchy Process (AHP) through the Super Decisions 2.10 application. The results show that the company is positioned in Quadrant I based on the SWOT analysis, with coordinates (x1.221; y0.638). Three SO strategies are produced: improving the quality and varieties of cut chrysanthemums, optimizing production and sales during major holidays, and strengthening marketing management. The AHP results indicate that the highest-priority strategy is optimizing production and sales during major holidays (weight 0.493), while the top sub-strategy is developing a structured planting and harvesting schedule (weight 0.337).